Revisiting the Spawning Pattern of Nyale Worms (Eunicidae) Using the Metonic Cycle - Imam Bachtiar; Shingo Odani (Ilmu Kelautan)
Mass spawning dates of nyale worms (Eunicidae) have been scientifically predictable since 2019. The month of spawning is consistently following the pattern of the February full moon, while the date of spawning is consistently on the 20th of the lunar calendar. There are particular years with February only spawning, March only spawning, and split spawning in both February and March. The existing prediction of the split spawning, however, was constructed with very little available data. The present study aimed to revisit the split spawning prediction using the Metonic cycle, a 19-year lunisolar cycle. The results show that the spawning prediction very much follows the Metonic Cycle. There are minor dates on split spawning to be revised, when February full moon rises on 14th February. The revised hypothesis is that split spawning is very likely to occur when the full moon rises between the 7th to 13th of February. When February full moon appears before the 7th of February, single spawning will take place on the fifth day after the March full moon.  When February full moon befalls after the 13th of February, single spawning will occur on the fifth day after the February full moon. The revised prediction method has only 2 (two) deviances in 114 years of simulation dates. The present study is the first to suggest the link between Polychaete spawning patterns and the Metonic Cycle.